Pemberdayaan Keluarga Tentang Pelaksanaan Senam Hamil Dalam Rangka Persiapan Persalinan - Ika Yuni Susanti; Farida yuliani (Jurnal Pengabdian Masyarakat, 2026)
Prenatal exercise is one of the activities in health services during pregnancy. The Indonesian Ministry of Health requires Minimum Service Standards containing 14 Steps Towards Integrated and Comprehensive Maternal Protection. Therefore, during ANC (Antenatal Care), Antenatal Education is provided, including prenatal exercise as part of the education for mothers as a form of